1994
DOI: 10.1002/1098-108x(199401)15:1<43::aid-eat2260150106>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Eating related and general psychopathology in obese females with binge eating disorder

Abstract: One hundred obese women with a mean age of 39.2 years, and a mean body mass index (BMI) of 35.9 kg/m2 were evaluated before entering a treatment study for weight reduction. According to the results of a structured interview, subjects were divided into four groups: (?) no overeating episodes, (2) episodic overeating episodes without the feeling of loss of control, (3) overeating plus the sense of loss of control (binge eating), and (4) full diagnostic criteria for binge eating disorder (BED). One‐way analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(135 citation statements)
references
References 37 publications
6
118
0
8
Order By: Relevance
“…This finding of a significant relationship between severity of binge eating and body weight supports the majority of existing research in this area (Brody et al, 1994;Bruce & Agras, 1992;de Zwaan et al, 1994;Fitzgibbon & Blackman, 2000;Kolotkin et al, 1987;Lowe & Caputo, 1991;Marcus et al, 1985;Spitzer et al, 1992Spitzer et al, , 1993Telch et al, 1988; , 1993). Although both frequency of binge eating episodes and amount of food consumed per episode are part of the diagnostic criteria for BED, the two variables were unrelated in the current study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This finding of a significant relationship between severity of binge eating and body weight supports the majority of existing research in this area (Brody et al, 1994;Bruce & Agras, 1992;de Zwaan et al, 1994;Fitzgibbon & Blackman, 2000;Kolotkin et al, 1987;Lowe & Caputo, 1991;Marcus et al, 1985;Spitzer et al, 1992Spitzer et al, , 1993Telch et al, 1988; , 1993). Although both frequency of binge eating episodes and amount of food consumed per episode are part of the diagnostic criteria for BED, the two variables were unrelated in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…The majority of studies in the current literature have reported a positive relationship between the severity of binge eating and body weight (Brody, Walsh, & Devlin, 1994;Bruce & Agras, 1992;de Zwaan et al, 1994;Fitzgibbon & Blackman, 2000;Kolotkin et al, 1987;Lowe & Caputo, 1991;Marcus et al, 1985;Spitzer et al, 1992Spitzer et al, , 1993Telch, Agras, & Rossiter, 1988;Yanovski et al, 1993), a few studies have found no such relationship (Goldfein et al, 1993;Gormally et al, 1982;Keefe et al, 1984;Striegel-Moore et al, 1998;Wadden et al, 1993;Wilson, Nonas, & Rosenblum, 1993), and none have implicated a negative relationship . Wadden et al (1993) noted that studies that reported a positive relationship between binge eating and adiposity evaluated samples with a greater weight range.…”
Section: Introductionmentioning
confidence: 92%
“…1b [47]. A growing body of literature suggests that ACT may be useful for managing or losing weight [48][49][50]. Second, the AI in Fig.…”
Section: Original Researchmentioning
confidence: 99%
“…Here, the decision to offer ACT to nonresponders with a history of emotional and binge eating is based on a conjecture that ACT may be particularly relevant for addressing this type of problem [49]. For example, ACT may be more useful than continued IBT or IBT+MR in resolving some of the problems associated with emotional or binge eating, such as feelings of ineffectiveness, perfectionist attitudes, impulsivity, low self-esteem, and poor sense of control [50].…”
Section: Original Researchmentioning
confidence: 99%
“…The comparison between obese with or without BE showed that the first group presented an earlier development of obesity and dietary behavior, as well as higher weight fluctuations. 28 A study carried out in the city of São Paulo (Brazil) with 217 women who were taking part in a weight reduction program, aged between 15-59 years (BMI > 25 kg/m²), showed that the BE was often reported. The women with BE presented a significantly higher BMI, several attempts to lose weight and weight fluctuation, depression and alexithymia (difficulty to express affection), compared to women without BE.…”
Section: Discussionmentioning
confidence: 99%